Müteselsil Kefalette Def’iler - Acar Ünal, Özlem (Seçkin Yayıncılık, 2018)
6098 sayılı Türk Borçlar Kanunu’nun yürürlüğe girmesiyle birlikte, kişisel bir teminat olan kefalet sözleşmesinde önemli bir takım değişiklikler yapılmıştır. Bu değişikliklerden bir kısmı, müteselsil kefalet sözleşmesine ilişkindir. Bu doğrultuda müteselsil kefil 818 sayılı Mülga Borçlar Kanunu zamanında sahip olmadığı bir takım yeni savunma imkanlarına kavuşmuştur. Müteselsil kefil, yalnızca müteselsil kefalet sözleşmesine özgü savunma imkanlarına başvurabileceği gibi genel olarak kefalet sözleşmesinden kaynaklanan diğer savunma imkanlarından da yararlanabilmektedir. Bunun dışında asıl borçlunun veya mirasçılarının sahip olduğu savunma imkanlarına da başvurabilmektedir. Ayrıca müteselsil kefilin alacaklıyla arasındaki kişisel ilişkilere dayanan savunmaları da söz konusu olabilmektedir.

A the Turkish Code of Obligations, numbered 6098, came into operation several amendments came into force in bailment contracts, which have personal guaranty involved. Some of these amendments are related to Joint Guaranty Agreements. Accordingly Joint Guarantor has the chance to have new rights of defence which he she didn’t have in time which the previous Turkish Code of Obligations, numbered 818, was in force. The Joint Guarantor can appeal for defence opportunities which are peculiar only to Joint Guaranty Agreements while he she also can appeal for any other defence opportunities which arise from bailment contracts in general. Besides he she also can appeal for any defence opportunities which the principal deptor or the inheritors have. Additionally the advocacy based on personal relationships between the joint guarantor and the oblige, can also be in question.
Exceptio Related to Joint Guaranty
Keywords: Müteselsil kefalet; Def'i; Rehin; Alacaklı; Kefil; Joint guaranty; Exceptio; Obligee; Bail